Interaction Between Rumen Microbiota and Epithelial Mitochondrial Dynamics in Tibetan Sheep: Elucidating the Mechanism of Rumen Epithelial Energy Metabolism - Ying Xu; Yuzhu Sha; Xiaowei Chen; Qianling Chen; Xiu Liu; Yanyu He; Wei Huang; Yapeng He; Xu Gao (BioTech, 2025)
Investigating the functional interactions between rumen microbial fermentation and epithelial mitochondrial dynamics/energy metabolism in Tibetan sheep at different altitudes, this study examined ultrastructural changes in rumen epithelial tissues, expression levels of mitochondrial dynamics-related genes (fusion: Mfn1, Mfn2, OPA1, Mic60; fission: Drp1, Fis1, MFF), and ketogenesis pathway genes (HMGS2, HMGCL) in Tibetan sheep raised at three altitudes (TS 2500m, TS 3500m, TS 4500m). Correlation analysis was performed between rumen microbiota/metabolites and mitochondrial energy metabolism. Results: Ultrastructural variations were observed across altitudes. With increasing altitude, keratinized layer became more compact; desmosome connections between granular layer cells increased; mitochondrial quantity and distribution in spinous and basal layers increased. Mitochondrial dynamics regulation: Fission genes (FIS1, DRP1, MFF) showed significantly higher expression at TS 4500m (p < 0.01); fusion genes (Mfn1, OPA1) exhibited altitude-dependent upregulation. Energy metabolism markers: Pyruvate (PA) decreased significantly at TS 3500m/TS 4500m (p < 0.01); citrate (CA) increased with altitude; NAD+ peaked at TS 3500m but decreased significantly at TS 4500m (p < 0.01); Complex II (SDH) and Complex IV (CO) activities decreased at TS 4500m (p < 0.01). Ketogenesis pathway: β-hydroxybutyrate increased significantly with altitude (p < 0.01); acetoacetate peaked at TS 2500 m/TS 4500 m; HMGCS2 expression exceeded HMGCL, showing altitude-dependent upregulation at TS 4500m (p < 0.01). Microbiome–metabolism correlations: Butyrivibrio_2 and Fibrobacter negatively correlated with Mic60 (p < 0.01); Ruminococcaceae_NK4A214_Group positively correlated with Mfn1/OPA1 (p < 0.05); WGCNA identified 17 metabolite modules, with MEturquoise module positively correlated with DRP1/Mfn2/MFF (p < 0.05). Conclusion: Altitude-induced ultrastructural adaptations in rumen epithelium correlate with mitochondrial dynamics stability and ketogenesis upregulation. Mitochondrial fission predominates at extreme altitudes, while microbiota–metabolite interactions suggest compensatory energy regulation mechanisms.